Kosher nation - Fishkoff, Sue (Schocken Books, 2010)
It's a kosher, kosher world : kosher food conquers the U.S. market -- Eating their way into Heaven : the who, what, and why of keeping kosher -- Big brother is watching : the kosher certification agencies -- On fire for kashrut : the life and times of a mashgiach -- Pastrami on rye : the Jewish deli -- Beyond Manischewitz : kosher wine aims high -- Goodbye Moishe's : supermarkets replace the corner store -- Killing it softly : kosher meat-who makes it, who eats it -- Please don't eat the broccoli : bug infestation takes salad off the table -- Made in China : kosher food production goes global -- A wedding in New Jersey : cholov yisroel to sushi, the new kosher diet -- Got shrimp? liberal Jews take another look at kashrut -- Kosher law and its discontents : who decides what's kosher? -- Postville : the scandal at agriprocessors changes the kosher conversation -- Eating their way into Heaven, part II : the new Jewish food movement